Static and Dynamic Distributional Effects of Decoupled Payments: Single Farm Payments in the European Union - Pavel Ciaian; D'Artis Kancs; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
This paper analyses the distributional effects of decoupled Single firm Payments (SFP) in the European Union. In a static world the SFP benefit only firmers, irrespective of the implemented SFP model and irrespective of whether entitlements are tradable or not, except when the size of the allocated entitlements is larger than the eligible area and/or if entrants are eligible for the SFP. Then the SFP gets either partially or fully capitalized into land values and landowners benefit. In a dynamic world the effects depend on the nature of structural change, on the tradability of entitlements, and on the implementation model.
Keywords: D23; D30; H21; Q12; Q18; 330; Land market; agricultural policy rents; decoupled subsidies; land capitalization; Agrarboden; Immobilienmarkt; Agrarsubvention; EU-Staaten